Sternocostoclavicular Hyperostosis: Positive Clinical and Radiological Response on Pamidronate - Leerling, Anne T.; Cañete, Ana Navas; Ramautar, Ashna I. E.; Appelman-Dijkstra, Natasha M.; Winter, Elizabeth M. (Frontiers in Endocrinology, 2021)
Background Sternocostoclavicular hyperostosis (SCCH) is a rare disease, constituting a chronic sterile osteomyelitis with elevated bone turnover in the axial skeleton, causing pain and shoulder dysfunction. SCCH severely interferes with daily activities, work, and quality of life. SCCH has a relapse-remitting disease course, but inflammatory-induced sclerotic transformation in the affected area is slowly progressive. Here we present two patients with clinical and radiological diagnosis of SCCH treated with intravenous pamidronate, leading to clinical remission in both, but complete resolution of sclerosis in one of them, which is a novel finding in our experience. Case Presentation Two adult female SCCH-patients presented with longstanding pain, swelling of the anterior chest wall, and compromised shoulder function. Subsequent single photon emission computed tomography-computed tomography (SPECT/CT) illustrated elevated bone activity and sclerosis in the SC region, with hyperostosis, confirming the diagnosis of SCCH. As symptoms in both patients were eventually refractory to standard painkillers such as non-steroidal anti-inflammatory drugs (NSAIDs), intravenous pamidronate treatment in 3-month cycles was started. Pamidronate was effective in reducing pain and improving shoulder function and also led to decreased bone turnover on skeletal scintigraphy. Sclerosis in the first patient persisted. In the second patient, however, a complete resolution of sclerosis was observed. Conclusions SCCH remains a rare bone disorder for which no evidence-based therapies are yet available. While disease burden is high, SCCH lacks recognition and is often diagnosed long after symptomatic presentation. As for the cases in this report, pamidronate was successful in reducing symptoms, and in the second case even led to regression of sclerotic changes on CT-imaging.